Corrosion fatigue performance of modified 17-4PH in simulated geothermal environment - Li, Zhipeng; Sun, Ming; Zhang, Hongguang; Xu, Weiwei; Wu, Lianlian (Frontiers in Materials, 2024)
Corrosion fatigue behavior of a new candidate material for geothermal turbine blade, modified 17-4PH, was investigated in detail. The environmental acceleration of crack growth rate was discussed in terms of ∆K. Fracture surface and side surface were observed by SEM. The crack path on side surface was also analyzed by EBSD. Then, the corrosion mechanism was discussed. Striation width on the fracture surface was compared to the crack growth per cycle. Since pitting occurred during the corrosion fatigue test, anodic polarization test was exercised to measure the pitting potential, and the cause for the pitting was also discussed. The hardness was also characterized by micro-hardness test and auger electron mapping.